Validation of the Overparenting Short-Form Scale with Parents of Early Adolescents: Factorial Structure, Measurement Invariance and Convergent Validity of the OP-SF - Yosi Yaffe (Psychiatry International, 2025)
Background: Overparenting describes a developmentally inappropriate and excessive parental involvement in a child’s life. It is predominantly measured in contemporary research by using emerging adults’ reports. Objective: The current study briefly reports on the adaptation and validation process of the overparenting short-form scale (OP-SF) with parents of early adolescents. The scale is among the sole instruments for evaluating overparenting within a general setting from the parental perspective. However, to date, its structure and psychometric properties remain untested among parents of pre-adults. Method: A cohort of 316 parents, including 159 mothers and 157 fathers (Mage = 44.07, SD = 5.08), provided online assessments regarding their overparenting behaviours, alongside a battery of related parental instruments used for validation. Results: The results showed that the OP-SF with three dimensions (i.e., Anticipatory Problem Solving, Affect Management, and Risk Aversion) fitted the data well, demonstrated measurement invariance across parental gender, had an acceptable internal consistency, and exhibited good convergent validity with several related constructs. Conclusions: Taken together, the 9-item OP-SF is a sound instrument for assessing a unidimensional construct of overparenting when used with parents of early adolescents. The implications for psychiatric and family practices involving parents and adolescents are discussed in depth.